Accounting for goodwill under FRS136 : case of Malaysian plantation companies - Yusof, Nurul Adillah; Ismail, Hashanah (David Publishing Company, 2010)
The introduction of FRS (financial reporting standards) 136 to Malaysian PLC’s (public limited company) in 2006 indirectly formalized accounting for purchased goodwill for the first time. Based on a sample of 2006 annual reports of 10 Main Board companies from plantation sector, the study finds the level of desired disclosure has yet to be met. Whilst the intention of the standard is noble, actual practice for first time reporting entities indicate that Malaysian PLC’s and their auditors have far to go before they can meet the expectation set by FRS 136 in particular and International Financial Reporting Standards in general.